RETRACTED ARTICLE: Effectiveness of Social Media Platforms in Disseminating Qur'anic Teachings among Contemporary Muslims - Sule, Muhammad Maga; Mainiyo, Attahir Shehu (UIN Antasari Banjarmasin, 2023)
Retraction Notice This article has been retracted from Alhadharah: Jurnal Ilmu Dakwah because the authors submitted the same work to multiple journals, resulting in duplicate publication. The article was first published in Spektra: Jurnal Ilmu-ilmu Sosial, Vol. 5 No. 1 (2023), pp. 47-64, on 22 September 2023, with the same title: